SISO and MIMO throughput analysis for long term evolution (LTE) / Siti Zuraini Harun - Harun, Siti Zuraini
This paper provides the analysis and comparison of data throughput in Long Term Evolution (LTE) between Single Input Single Output (SISO) and Multiple Input Multiple Output (MIMO). LTE utilizes MIMO data transmission such as Open Loop (OL) Spatial Multiplexing, Close Loop (CL) Spatial Multiplexing, Transmit Diversity and Single Input Multiple Output (SIMO) in achieving higher data throughput and channel capacity as compared to SISO conventional transmission scheme. Based on the results obtained using base station emulator equipment, the performance of physical layer data throughput is evaluated for different conditions and scenarios, which the following arc being considered such as various antenna diversity schemes for instance 2x2 antenna configuration, different modulation, coding schemes, bandwidth and resource block. The effect of changing the mentioned parameters will result to a different throughput and impact radio performance. For this, a thorough analysis has been done comparing both cases SISO and MIMO using a commercial LTE device which is now available in the market. The performance study and test includes FDD operational mode for uplink and downlink transmission.